Perilaku Gizi Remaja Putri Terhadap Zat Anti Gizi Dan Kaitannya Dengan Anemia Di SMAN 1 Kelapa, Bangka Barat - Enardi, Ori Pertami; Wardani, Zenderi; Ratmawati, Ratmawati; Virmando, Eri; Febriani, Jenisya (JGK: Jurnal Gizi dan Kesehatan, 2025)
Anemia remains a major public health issue among adolescent girls in Indonesia. This study aimed to analyze the relationship between knowledge, attitudes, and practices (KAP) regarding anti-nutritional substances and anemia status among female students aged 15–18 years at SMAN 1 Kelapa, West Bangka. A cross-sectional design was used with 48 randomly selected participants. Data were collected through structured questionnaires and secondary hemoglobin data from the Aksi Bergizi screening. Results showed an anemia prevalence of 41.7%, with median knowledge, attitude, and practice scores of 9, 10, and 7, respectively. Spearman correlation analysis revealed no significant relationship between KAP and anemia status (p > 0.05). These findings suggest that knowledge, attitude, and practice concerning anti-nutrients are not the main determinants of anemia. Interventions should also address other contributing factors such as iron intake, menstrual patterns, and overall nutritional status